Prioritization of Sustainable Water Management Strategies in Arid and Semi-Arid Regions Using SWOT Coupled AHP Technique to addressing SDGs - Mohammad Ebrahim Banihabib; Arash Noori; Luboš Jurík; Luboš Jurík; Nargis Mirzaie (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: Water shortage in arid regions should be addressed strategically. The proposes a framework for determining and prioritizing sustainable water management strategies based on Sustainable Development Goal 6.